Prevalence and predictors of sex under the influence of psychoactive substances among young people in informal settlements in Kampala, Uganda - Tonny Ssekamatte; Aisha Nalugya; Richard K. Mugambe; Brenda Wagaba; Doreen Nakalembe; Aloysius Mutebi; Richard Asaba Bagonza; Arnold Tigaiza; Winnifred K. Kansiime; Richard Ssempala; Solomon T. Wafula; John Bosco Isunju; et al. (BMC, 2023)
Abstract Background The use of psychoactive substances such as alcohol, heroin and marijuana is associated with negative health outcomes such as sexual violence and unintended pregnancies, and risky sexual behaviours. Although there is evidence linking psychoactive substance use and risky sexual behaviours such as inconsistent condom use and multiple sexual relationships, there is limited data on sex under the influence of psychoactive substances among young people. This study aimed to investigate the prevalence and predictors of sex under the influence of psychoactive substances among young people in informal settlements in Kampala, Uganda. Methods A cross-sectional study was conducted among 744 sexually active young psychoactive substance users in informal settlements in Kampala, Uganda. Data were collected through face-to-face interviews using a digitalized structured questionnaire, preloaded on the Kobocollect mobile application. The questionnaire captured data on the socio-demographic characteristics of the respondents, history of psychoactive substance use, and sexual behaviours. Data were analysed using STATA Version 14.0. A modified Poisson regression model was used to determine the predictors of sex under the influence of psychoactive substances.. Adjusted prevalence ratios at a p-value value ≤ 0.05 with a 95% confidence interval were considered. Results About 61.0% (454/744) of the respondents had had sex under the influence of psychoactive substances in the last 30 days. The predictors of sex under the influence of psychoactive substances were being female (PR 1.18, 95% CI: 1.04-1.34), being 20-24 years of age (PR: 1.22, 95% CI: 1.04-1.44), being married (PR 1.15, 95% CI: 1.01-1.31) or divorced/separated (PR 1.43, 95% CI: 1.26-1.61), not living with biological parents or guardians (PR 1.22, 95% CI: 0.99-1.50), earning 71 USD and below (PR 0.86, 95% CI: 0.79-1.03) and using alcohol (PR 1.43, 95% CI: 1.25-1.69), marijuana (PR 1.16, 95% CI: 1.02-1.31) and khat (PR 1.25, 95% CI: 1.10-1.42) in the last 30 days. Conclusion The study found that a high proportion of sexually active young people in informal settlements in Kampala, Uganda had engaged in sex under the influence of psychoactive substances in the past 30 days. The study also identified several factors associated with sex under the influence of psychoactive substances, including being female, being aged 20-24 years, being married or divorced or separated, not living with biological parents or guardians, and using alcohol, marijuana, or khat in the past 30 days. Our findings suggest the need for targeted sexual and reproductive health programs that incorporate risk-reduction interventions aimed at reducing sex under the influence of psychoactive substances, especially among females and those who do not live with their parents.